(untitled) (Global Journal of Science Frontier Research, 2016)
Parkia biglobosa (Jacq) is a perennial tree of considerable multipurpose importance. In Nigeria, over 60 million people depend on it for food, fuel, wood work and income. This priority tree with enormous economic and social values to the local people of Cross River State (North) is rapidly declining due to rapid human population growth, livestock population pressures, increasing land fragmentation, over exploitation for seed (food) and a high demand for wood fuel especially charcoal. In view of this, a survey was carried out in the Guinea Savanna of Cross River State (North) to determine the level of abundance (A) or rarity (R) of the specie. In each site, ten 20m × 20m randomly selected points were laid along four 1km line transect and accordingly assessed. Seventeen economic important trees were assessed and counted as present with particular emphasis on P. biglobosa (taking into consideration the age of the plant). Results showed that the tree was rare (R) and facing extinction with low densities of 2.1/ha for (Ogoja L.G.A), 1.6/ha (Bekwarra), 2/ha (Obudu), 1.7/ha (Obanliku) and 1.5/ha for (Yala).